A Class of Fractional p-Laplacian Integrodifferential Equations in Banach Spaces - Yiliang Liu; Liang Lu (Abstract and Applied Analysis)
We study a class of nonlinear fractional integrodifferential equations with p-Laplacian operator in Banach space. Some new existence results are obtained via fixed point theorems for nonlocal boundary value problems of fractional p-Laplacian equations. An illustrative example is also discussed.